Inhibition of Exosome Release Sensitizes U937 Cells to PEGylated Liposomal Doxorubicin - Hekmatirad, Shirin; Moloudizargari, Milad; Moghadamnia, Ali Akbar; Kazemi, Sohrab; Mohammadnia-Afrouzi, Mousa; Baeeri, Maryam; Moradkhani, Fatemeh; Asghari, Mohammad Hossein (Frontiers in Immunology, 2021)
Aims: Acute myeloblastic leukemia (AML) is the most common type of acute leukemia in adults. Despite numerous treatment strategies a large number of patients do not respond to treatment and experience relapse. The main problem of these patients is the development of resistance to anti-cancer drugs. Therefore, any endeavor to reduce drug resistance in these patients is of high priority. In this context, evidence suggests that exosomes could reduce drug resistance by removing drugs from their parent cells. In the present study, we aimed to investigate the effects of exosome release inhibition on the resistance of U937 cells to PEGylated liposomal doxorubicin (PLD). Main methods: In order to find a suitable ABCG2 transporter substrate, virtual screening was performed and PLD was selected. U937 cells were treated with PLD with/without co-treatment with the exosome release inhibitor, GW4869. Released exosomes within different study groups were isolated and characterized to determine the differences between groups. Finally, the effect of exosome inhibition on the cytotoxicity of PLD on U937 cells was determined using different cytotoxicity assays. Key findings: GW4869 treatment caused a significant decrease in the exosome release of U937 cells compared to the untreated cells (P<0.05). Co-treatment with GW4869 significantly increased cytotoxic cell death in the groups treated with 0.5 and 1 µM PLD, compared to the same groups without GW4869 co-treatment (P<0.05). Interestingly, co-treatment with GW4896 and 0.5 µM PLD was enough to induce the same cytotoxic effect as that of the sole 1 µM PLD. Significance: Our findings showed that inhibition of exosome release could prevent PLD efflux and consequently increase the vulnerability of the U937 cells to the cytotoxic effects of PLD. Our results indicate that the integration exosome release inhibitors into the common PLD-containing chemotherapy regimens could significantly lower the required concentrations of the drug and consequently reduce its associated side effects.